Pengujian Gel Antiseptik Infusa Daun Kelor Terhadap Jumlah Angka Kuman Serta Evaluasi Fisik Sediaannya - Asiska Permata Dewi; Kony Putriani; Yulia Yesti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Moringa leaves (Moringa oleifera L.) is a plant which has benefit as anti-bacteria, anti-inflammation, and virus infection. Moringa leaves contain secondary metabolic compounds such as flavonoids, phenol, tannin, saponin, alkaloids, and triterpenoids. This research aimed to find out the effectiveness of the antiseptic gel of moringa leaves infusion on the number of germs, and its physical preparation and evaluation. The research method carried out on testing the number of germs was by counting the number of bacteria colonies which still grow in Nutrient Agar media after smeared with antiseptic gel of moringa leaves infusion, then evaluated for its physics gel trait covering organoleptic, pH, homogeneity, spreadability, and consistency. The testing result showed that in the germ count test at F1, F2, and F3, the average bacteria colony which still grew after incubation was in the amount of 137, 113, and 49 colonies. Testing in the positive control (Nuvo®) and negative control (gel basis), the average bacteria colony which still grew were in the amount of 17 and 173 colonies. The organoleptic test showed the gel form as semi-solid, greenish in colour, and the typical smell of moringa leaves, pH was in the range of 4,5 – 6,5, not seen coarse grain in gel preparations (homogeneous), spreadability around 5,1 cm – 5,5 cm and phase separation did occur in consistency test. Thereby, the higher the infusion concentration of moringa leaves in antiseptic gel, then the better its antiseptic effectiveness.